Chinese tourism in Spain: an analysis of the tourism product, attractions and itineraries offered by chinese travel agencies - Lojo, Aureli (Cuadernos de Turismo, 2016)
Analysis of the characteristics of tourism in China, and the evolution of Spain as an international destination, illustrates the importance of understanding Chinese outbound tourism and its implications for the Spanish tourism industry. The results of the paper present the characteristics of the tourism product offered by Chinese travel agencies. The study also indicates the itineraries, the main destinations within Spain and the distinctive elements of Spain that are valued by the tour operators. The purposes of this study are (1) to identify the patterns of the tourist groups from China to Spain and (2) to understand the characteristics of the tour packages offered by Chinese travel agencies.